PENGARUH MOTIVASI KERJA TERHADAP KINERJA PEGAWAI DI KANTOR CAMAT IDANOTAE KABUPATEN NIAS SELATAN - Nuriman Bawamenewi (LPPM Universitas Nias Raya, 2022)
The purpose of this study is to find out the effect of work motivation on employee performance in the Idanotae Camat Office of South Nias Regency. The type of research used is a quantitative type of causal nature. The data source was from employees, with the population and sample in the study being 32 people. Data collection techniques are research instruments or questionnaires. The data analysis method used is a simple linear regression analysis. The results of this study show that the value of motivation. This research can be concluded that there is a positive and significant influence on the performance of employees in the Idanotae Camat Office of South Nias Regency.